Protein carbamylation in atherosclerotic plaques correlates with uremia and disease progression, localizing predominantly to foam cells - Saar-Kovrov, Valeria; Pawlowska, Aleksandra; Guillot, Adrien; Gijbels, Marion J. J.; Sluimer, Judith C.; Temmerman, Lieve; Goossens, Pieter; Mees, Barend M. E.; Tacke, Frank; Jankowski, Vera; Jankowski, Joachim; Donners, Marjo M. P. C.; et al. (Frontiers in Immunology, 2025)
IntroductionCarbamylation is a non-enzymatic post-translational protein modification common in patients with uremia that causes pro-atherogenic alterations in plasma proteins. It is abundantly present in late-stage atherosclerotic plaques; however, the pathogenic relevance and functional consequences of this accumulation are not known.MethodsHuman atherosclerotic plaque tissue samples were stratified by plaques’ stage and kidney function.ResultsImmunohistochemistry revealed a significantly higher carbamylated lysine (carb-lys) abundance in latestage hemorrhaged plaques of chronic kidney disease patients compared to early-stage plaques, and a significant negative correlation to glomerular filtration rate for the advanced plaques. While we saw the difference in the total levels of carbamylation between early and advanced plaques, cellular carbamylation signal, studied in a parallel cohort of stable vs unstable plaques, did not differ between plaque stages but significantly correlated to CD68, PLIN2, and LGALS3 signals. Functional effects of carbamylated LDL (carbLDL) uptake on macrophages were studied in vitro on an in-house developed confocal-based microscale multi-assay platform to screen multiple cellular functions and demonstrated similar foam cell formation compared to the uptake of oxidized LDL (oxLDL). However, in contrast to oxLDL, carbLDL did not induce PPARg reporter gene expression, suggesting differential capacity to induce lipogenic pathways. Moreover, unlike oxLDL, carbLDL did not induce apoptosis or ROS production.DiscussionTaken together, our findings demonstrate an accumulation of carbamylated protein during plaque progression in patients with reduced kidney function. This can be, at least partially, explained by uptake of carbLDL particles by the macrophages. CarbLDL uptake, in turn, can induce foam cell formation but seems less cytotoxic than oxLDL.